Announcements, Conferences, Exhibitions. (Religion & the Arts, 2003)
Provides information on announcements, conferences, and exhibitions related to religion and the arts as of December 2003. A Narratable World: The Theological Implications of Story; The Newman of the Apologia and the Newman of History; The Festival of Faith and Writing.